Downstream industrial biotechnology recovery and purification - Flickinger, Michael C. (Canda : Wiley, John Wiley & Sons, 2013)
"Universities worldwide are establishing biomanufacturing centers, and demand is growing for a workforce trained in this discipline. Downstream Recovery and Purification is an affordable, accessible desk reference on biomanufacturing for professionals, instructors, and students. With information on equipment, process and facility design, cGMP operation, and regulatory compliance, it is based on Wiley's 7-volume Encyclopedia of Industrial Biotechnology, Bioprocess, Bioseparation, and Cell Technology and features more than 50 carefully selected articles. Students and professionals alike will value this practical guide"--
"The 50 article reference work provides information on downstream recovery of cells and protein capture, process development and facility design, equipment, cGMP operations, and regulatory compliance"--
vol.1 :Expression systems and process development vol.2 : Equipment ,process design, sensing,control, and cGMP operation . vol.3 : Recovery and purification.
Includes bibliographical references and index.
All age.
Keywords: Biotechnology -- Encyclopedias; SCIENCE / Biotechnology